THE ROLE OF STORE LOCATION AND STORE ATMOSPHERE ON CUSTOMER LOYALTY - Azis, Abdul; Hermina, Nurul (PT. Altin Riset Publishing, 2024)
The coffee shop business in Indonesia has become a trend in recent years. Osiris Coffee is a business unit that provides customers with services and products. Over the last six months, Osiris Coffee has experienced a decline in the number of customers, which is believed to be due to the coffee shop's less strategic location and atmospheric store, which cannot compete with other coffee shops. This research aims to determine the effect of location and store atmosphere on customer loyalty at Osiris Coffee. It is quantitative and uses an Osiris Coffee customer analysis unit. Data was collected by distributing questionnaires to 84 customers. The results of hypothesis testing state that store location has a partial effect on customer loyalty, and store atmosphere has a partial effect on customer loyalty. Apart from that, store location and store atmosphere simultaneously positively and significantly affect customer loyalty. The results of hypothesis testing in this research have a positive effect both partially and simultaneously.